Brain Neural Activity Patterns in an Animal Model of Antidepressant-Induced Manic Episodes - Chen, Min; Chen, Guangdong; Tian, Hongjun; Dou, Guangqian; Fang, Tao; Cai, Ziyao; Cheng, Langlang; Chen, Suling; Chen, Ce; Ping, Jing; Lin, Xiaodong; Chen, Chunmian; et al. (Frontiers in Behavioral Neuroscience, 2022)
Background: In the treatment of patients with bipolar disorder (BP), antidepressant-induced mania is usually observed. The rate of phase switching (from depressive to manic) in these patients exceeds 22%. The exploration of brain activity patterns during an antidepressant-induced manic phase may aid the development of strategies to reduce the phase-switching rate. The use of a murine model to explore brain activity patterns in depressive and manic phases can help us to understanding the pathological features of BP. The novel object recognition preference ratio is used to assess cognitive ability in such models. Objective: To investigate brain Ca2+ activity and behavioral expression in the depressive and manic phases in the same murine model, to aid understanding of brain activity patterns in phase switching in BP. Methods: In-vivo two-photon imaging was used to observe brain activity alterations in a murine model in which induce depressive-like and manic-like behaviors were induced sequentially. The immobility time was used to assess depressive-like symptoms and the total distance traveled was used to assess manic-like symptoms. Results: In-vivo two-photon imaging revealed significantly reduced brain Ca2+ activity in temporal cortex pyramidal neurons in the depressive phase in mice exposed to chronic unpredictable mild stress compared with naïve controls. The brain Ca2+ activity correlated negatively with the novel object recognition preference ratio within the immobility time. Significantly increased brain Ca2+ activity was observed in the ketamine-induced manic phase. However, this activity did not correlate with the total distance traveled. The novel object recognition preference ratio correlated negatively with the total distance traveled in the manic phase. Conclusions: In this study, we observed brain Ca2+ activity in an animal model of BP with a chronic unpredictable mild stress–induced depressive phase and a subsequent antidepressant-induced manic phase. In the depressive phase, brain neural activity alterations correlated with depressive symptoms and cognitive impairment. In the manic phase, cognitive impairment, but not brain neural activity, correlated with manic symptoms. Findings from this animal study expand our understanding of phase-switching mechanisms in patients with BP, but further research is needed.